Pengaruh Program Bos terhadap Keputusan Anak Putus Sekolah - Rahmawati, Pramudina (Universitas Negeri Semarang, 2020)
This study aims to analyze the influence of the BOS Program on junior high school dropout decisions in Purworejo Regency and analyze individual, family and school characteristics of junior high school dropout decisions in Purworejo Regency. This type of research is quantitative. The population used in this study were all junior high school children in Purworejo Regency with 24,827 students graduating from junior high school and 30 students dropping out of school. Data analysis method used in this study is binary logit regression. The results in this study indicate that the BOS Program has no significant effect on the decision of school dropouts because BOS funds cannot cover all school operational costs so that many school fees are charged to parents and there are other factors that cause children's decision to drop out of school. Individual characteristics in the form of education and health perceptions significantly influence the decision of school dropouts. Family characteristics in the form of the number of siblings, siblings drop out of school, help parents, and academic support of parents significantly influence the decision of children dropping out of school. School characteristics such as problems with teachers, problems with friends, and distance do not have a significant effect, while school dropouts have a statistically significant effect on the decisions of dropouts. Penelitian ini bertujuan untuk menganalisis pengaruh Program BOS terhadap keputusan anak putus sekolah tingkat SMP di Kabupaten Purworejo dan menganalisis karakteristik individu, keluarga dan sekolah terhadap keputusan anak putus sekolah tingkat SMP di Kabupaten Purworejo. Jenis penelitian ini adalah kuantitatif. Populasi yang digunakan dalam penelitian ini adalah seluruh anak sekolah menengah pertama di Kabupaten Purworejo dengan anak yang lulus sekolah menengah pertama sejumlah 24.827 siswa dan anak putus sekolah sebanyak 30 siswa. Metode analisis data yang digunakan dalam penelitian ini adalah regresi binary logit. Hasil dalam penelitian ini menunjukkan bahwa Program BOS tidak berpengaruh signifikan terhadap keputusan anak putus sekolah karena dana BOS tidak dapat menutup semua biaya operasional sekolah sehingga banyak biaya sekolah yang dibebankan kepada orang tua siswa serta terdapatnya faktor lain yang menyebabkan keputusan anak untuk putus sekolah. Karakteristik individu berupa persepsi pendidikan dan kesehatan berpengaruh signifikan terhadap keputusan anak putus sekolah. Karakteristik keluarga berupa jumlah saudara, saudara kandung putus sekolah, membantu orang tua, dan dukungan akademik orang tua berpengaruh signifkan terhadap keputusan anak putus sekolah. Karakteristik sekolah berupa masalah dengan guru, masalah dengan teman, dan jarak tidak berpengaruh signifikan, sedangkan teman putus sekolah berpengaruh signifikan secara statistik terhadap keputusan anak putus sekolah.